Challenges in diagnosis of atypically localised hydatid cysts in children: Experiences in two university hospitals - Tartar, Tugay; User, Idil Rana; Bakal, Ünal; Saraç, Mehmet; Özokutan, Bülent Hayri; Kazez, Ahmet (Logos Medical Publishing, 2019)
Objective: Hydatid cysts localised outside the liver and lungs are defined as atypically localised hydatid cysts and account for 10% of all cases. In this study, it was aimed to evaluate atypically localised hydatid cyst cases and especially investigate the challenges during diagnosis.Materials and Methods: Age, gender, complaints, location of lesions, laboratory results, presence of ruptured cyst, complications, treatment method, follow-up periods and development of recurrence were retrospectively examined in patients followed-up and treated for atypically localised hydatid cyst in two university hospitals between January 2000 and December 2017. Results: Among a total of 139 hydatid cyst patients, atypically localised hydatid cyst was diagnosed in 14 cases (eight males, six females). The mean age of the cases was 10.9±2.9 years. Six solitary atypically localised hydatid cysts were located in the spleen, and each one of them in the kidney, urachus, omentum and retrovesical space. There was multiple organ involvement in four (28.6%) cases. The most common complaints were abdominal pain and fatigue, and the most common physical examination findings were abdominal tenderness and guarding. Eosinophilia was not observed in any of the cases (n:10) with solitary atypical involvement. The sensitivity of indirect haemagglutination test was 67.5% for solitary atypically localised hydatid cyst. In cases localized in omentum, urachus and retrovesical space radiological evaluation did not contribute to the diagnosis. The diagnostic sensitivity of ultrasonography and computed tomography were 78.5, and 80%, retrospectively. The cases were postoperatively followed up for a median period of 12 (6-36) months. and recurrence was not seen. Conclusion: Atypically localised hydatid cyst should be considered in cysts diagnosed radiologically in different organs even when serology is negative without any specific physical examination finding. Multiorgan involvement is more common in atypically localised hydatid cyst. © 2019 Turkey Association of Pediatric Surgery.
Çocuklarda atipik yerleşimli kist hidatik tanisinda yaşanan zorluklar: Iki üniversite hastanesi deneyimi
Keywords: Atypical localization; Child; Hydatid cyst